2016
DOI: 10.3892/ol.2016.5121
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin α1 therapy subsequent to radical hepatectomy in patients with hepatitis B virus-associated hepatocellular carcinoma: A retrospective controlled study

Abstract: Abstract. The clinical efficacy of thymosin α1 (Tα1) therapy in patients with hepatocellular carcinoma (HCC) subsequent to radical hepatectomy is unclear. In the present study, the impact of Tα1 therapy on outcomes in HCC patients after radical hepatectomy was retrospectively evaluated. Medical records were retrospectively reviewed for 146 patients with hepatitis B virus (HBV)-associated HCC who were treated by radical hepatectomy and subsequently with Tα1 therapy, as well as for 412 control patients with HBV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Although these clinical outcomes were not systematically reviewed, one study included in this meta-analysis reported that ETV plus Tα1 combination group had a lower incidence of HCC after treatment of 51 weeks, and yet had no bene ts in clinical outcomes regarding ascites, hepatic encephalopathy, variceal hemorrhage and liver stiffness, in comparison with ETV alone group [26]. The results were consistent with the study of Liang YR, which indicated that Tα1 therapy improves liver function and obviously extend recurrence-free and overall survival for patients with HBV-related HCC [37]. Unfortunately, the participants of RCTs were from Chinese mainland.…”
Section: Discussionsupporting
confidence: 71%
“…Although these clinical outcomes were not systematically reviewed, one study included in this meta-analysis reported that ETV plus Tα1 combination group had a lower incidence of HCC after treatment of 51 weeks, and yet had no bene ts in clinical outcomes regarding ascites, hepatic encephalopathy, variceal hemorrhage and liver stiffness, in comparison with ETV alone group [26]. The results were consistent with the study of Liang YR, which indicated that Tα1 therapy improves liver function and obviously extend recurrence-free and overall survival for patients with HBV-related HCC [37]. Unfortunately, the participants of RCTs were from Chinese mainland.…”
Section: Discussionsupporting
confidence: 71%
“…Although these clinical outcomes were not systematically reviewed, one study included in this meta-analysis reported that ETV plus Tα1 combination group had a lower incidence of HCC after treatment of 51 weeks, and yet had no benefits in clinical outcomes regarding ascites, hepatic encephalopathy, variceal hemorrhage and liver stiffness, in comparison with ETV alone group [26]. The results were consistent with the study of Liang YR, which indicated that Tα1 therapy improves liver function and obviously extend recurrence-free and overall survival for patients with HBV-related HCC [37]. Unfortunately, the participants of RCTs were from Chinese mainland.…”
Section: Discussionsupporting
confidence: 69%
“…As compared to patients that received only liver resection, patients treated with Tα1 had higher overall survival and recurrence-free survival, together with a reduced neutrophil-to-lymphocyte ratio, pointing to the use of Tα1 in patients at high risk for recurrence after resection (71). The administration of Tα1 also proved effective in improving liver function and increasing overall survival and recurrence-free survival in a retrospective study evaluating patients with HBV-associated HCC after radical hepatectomy (72).…”
Section: Thymosin α1 and Hepatocellular Carcinomamentioning
confidence: 99%